2022
DOI: 10.3390/toxins14070451
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Therapy for Spasmodic Dysphonia in Japan: The History and an Update

Abstract: Spasmodic dysphonia (SD) is a rare neurological disorder that impairs phonatory function by triggering involuntary and intermittent contractions of the intrinsic laryngeal muscles. SD is classified into three types: adductor SD (AdSD), abductor SD (AbSD), and mixed SD. Of these, AdSD accounts for 90–95% of disease; younger females are predominantly affected. Botulinum toxin injection into the laryngeal muscles is safe, minimally invasive, and very effective. Here, we review the history of clinical research for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…1984 Laryngeal injection of BT to treat spasmodic dysphonia was first performed by Blitzer et al Thereafter, hundreds of articles were published; most reporting it to be effective [1]. 1990 The American Academy of Neurology and the American Academy of Ophthalmology and Otolaryngology suggested that BT could be safely and effectively used for various hyperkinetic diseases.…”
Section: H L I I G G H H T Smentioning
confidence: 99%
“…1984 Laryngeal injection of BT to treat spasmodic dysphonia was first performed by Blitzer et al Thereafter, hundreds of articles were published; most reporting it to be effective [1]. 1990 The American Academy of Neurology and the American Academy of Ophthalmology and Otolaryngology suggested that BT could be safely and effectively used for various hyperkinetic diseases.…”
Section: H L I I G G H H T Smentioning
confidence: 99%
“…SD can be further classified based on the affected muscle groups as either adductor spasmodic dysphonia (ADSD), abductor spasmodic dysphonia (ABSD), or mixed-type dysphonia, with ADSD being the most common subtype (accounting for 90–95% of cases) [ 4 ]. The irregular voice breaks caused by laryngeal muscle spasms have been shown to significantly impair patient quality of life, leading to decreased work attendance and performance [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These neurotoxins act on the peripheral nervous system, where they inhibit the release of acetylcholine (ACh) from the synaptic terminal of neuromuscular junctions. 15,16 Currently, BoNT type A injections are a popular non-surgical and non-invasive treatment to optimize and change an individual's facial appearance and achieve rejuvenation. 17 In this study, we aimed to demonstrate the efficacy of anticholinesterase inhibitor pyridostigmine in accelerating spontaneous recovery following botulinum toxin injections in a rabbit model.…”
Section: Introductionmentioning
confidence: 99%